Application of Ultrasonic Methods for Evaluation of High-Pressure Physicochemical Parameters of Liquids - KIEŁCZYNSKI, Piotr; PTASZNIK, Stanisław; SZALEWSKI, Marek; BALCERZAK, Andrzej; WIEJA, Krzysztof; ROSTOCKI, Aleksander J. (Archives of Acoustics, 2019)
An emerging ultrasonic technology aims to control high-pressure industrial processes that use liquids at pressures up to 800 MPa. To control these processes it is necessary to know precisely physicochemical properties of the processed liquid (e.g., Camelina sativa oil) in the high-pressure range. In recent years, Camelina sativa oil gained a significant interest in food and biofuel industries. Unfortunately, only a very few data characterizing the high-pressure behavior of Camelina sativa oil is available. The aim of this paper is to investigate high pressure physicochemical properties of liquids on the example of Camelina sativa oil, using efficient ultrasonic techniques, i.e., speed of sound measurements supported by parallel measurements of density. It is worth noting that conventional low-pressure methods of measuring physicochemical properties of liquids fail at high pressures. The time of flight (TOF) between the two selected ultrasonic impulses was evaluated with a cross-correlation method. TOF measurements enabled for determination of the speed of sound with very high precision (of the order of picoseconds). Ultrasonic velocity and density measurements were performed for pressures 0.1–660 MPa, and temperatures 3–30°C. Isotherms of acoustic impedance Z_a, surface tension σ and thermal conductivity k were subsequently evaluated. These physicochemical parameters of Camelina sativa oil are mainly influenced by changes in the pressure p, i.e., they increase about two times when the pressure increases from atmospheric pressure (0.1 MPa) to 660 MPa at 30°C. The results obtained in this study are novel and can be applied in food, and chemical industries.